Peran Unit Pelayanan Perempuan Dan Anak Terhadap Korban Human Trafficking Perspektif Maqāșid Shariah - Mulyono Mulyono (MAQASID, 2018)
ABSTRACTIn this research there are two formulation of the problem including: How is the Role of the PPA Unit in dealing with victims of Human Trafficking problems? What is the Role of the PPA Unit in dealing with victims of the Maqāșid Shariah Perspective? This research aims to determine the role of the PPA Unit against someone who is a victim of the crime of Human Trafficking and to find out how that role is in the view of Maqāșid Shariah.This type of research is field research that collects primary data through interviews with the Head of the PPA Unit, PPA Assist Investigator. The secondary data is obtained from the literature on Human Trafficking, PPA Unit Profiles, and Maqāșid Shariah. After the data is collected, then it is analyzed qualitatively and described descriptively.The Women's and Children's Services Unit has two roles, namely the handling of perpetrators and victims. In handling the Role perpetrators carried out in accordance with the Law. For victim handlers, the PPA Unit collaborates with PPT (Integrated Service Centers) and NGOs (Non-Governmental Organizations). In the view of Maqāșid Shariah the role carried out by the PPA Unit on victims fulfills five aspects in Maqaṣid Shariah, namely: Ḥifẓ Al-Aql, Ḥifẓ An-Nafș dan Ḥifẓ Ad-Din, Ḥifẓ Al-Māl, Ḥifẓ An-Nașb. Key words: Human Trafficking, PPA unit, Maqaṣid Shariah.